Forward and Backward Chaining in Linear Logic (Extended Abstract) - Harland, James A.; Pym, David J.; Winikoff, Michael (Electronic notes in theoretical computer science, 2000)
Logic programming languages based on linear logic are of both theoretical and practical interest, particularly because such languages can be seen as providing a logical basis for programs which execute within a dynamic environment. Most linear logic programming languages are implemented using standard resolution or backward chaining techniques. However, there are many applications in which the combination of such techniques with forward chaining ones are desirable. We develop a proof-theoretic foundation for a system which combines both forms of reasoning in linear logic.